EFEKTIFITAS PENGGUNAAN BANTUAN KEUANGAN PARTAI POLITIK DALAM PELAKSANAAN PROGRAM PENDIDIKAN POLITIK (Studi Kasus Partai Golongan Karya Kabupaten Bolaang Mongondow Tahun 2018) - Gabriel Marjulando Tangkere; Daud Markus Liando; Johny Pieter Lengkong (Sam Ratulangi University, 2021)
This study aims to determine the effectiveness of the use of political party financial assistance in the implementation of the political education program of the DPD II Golkar Bolmong Party in 2018. The research was carried out at the Secretariat Office of the DPD II Golkar Party, Bolaang Mongondow Regency. The method used in this research is a qualitative research method. Sources of research data consist of primary data and secondary data that are focused on aspects of effectiveness, namely aspects of tasks and functions, aspects of plans or programs, aspects of provisions and regulations, and aspects of goals and ideal conditions. The research informants amounted to 5 informants consisting of the Secretary of the DPD II Golkar Bolmong Party, the Treasurer of the DPD II Golkar Bolmong Party, the Chair of the Cadreization and Membership of the Golkar Bolmong Party, the Head of Education and Scholars, and the Chairman of the PK DPD II Golkar Bolmong Party. Data was collected by means of observation, interviews and documentation which were analyzed by means of data reduction, data presentation and drawing conclusions. The validity of the data is done by triangulating the data. The results showed that the effectiveness of political party financial assistance from the aspect of tasks and functions as well as aspects of the plan or program had not been effective, then from the aspect of the provisions it was effective but from the regulatory aspect as well as the aspect of objectives or ideal conditions it was not yet effective.